Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens - Dépatie, Sylvie; Desbarats, Catherine MacLeod; Gauvreau, Danielle; Lalancette, Mario; Wien, Thomas (McGill-Queen's University Press, 1998)
Keywords: Histoire; Historiens

Introduction: Habitants, marchands, historiens - Wien, Thomas (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Histoire; Historiens

Jardins et vergers à Montréal au XVIIIe siècle - Dépatie, Sylvie (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Jardins

Vingt ans d'études sur la population pendant le Régime français: bilan et perspectives - Gauvreau, Danielle (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)

Savage / Saint: The Lives of Kateri Tekakwitha - Greer, Allan (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Autochtones; Iroquois

The Merchant in the History of the "First Canada" - Miquelon, Dale (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Marchands

The Trade Assortment: The Meanings of Merchandise in the Ojibwa Fur Trade - White, Bruce M. (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Autochtones; Fourrure; Marchands

De la ville-comptoir à la ville fortifiée: évolution de la forme urbaine de Montréal au XVIIe siècle - Lalancette, Mario; Stewart, Alan M. (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Cartes et plans; Fortifications; Seigneurie